The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/eji.200939973
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of cross‐priming during virus infection is not directly linked to the ability of the antigen to be cross‐presented

Abstract: The initiation of CD8 1 T cell (CTL) immune responses can occur via cross-priming. Recent data suggested a relationship between cross-presentation and immunodominance of epitope-specific T cells. To test this association, we evaluated the efficacy of crosspresentation for several virus epitopes in vitro and examined if this can be extrapolated in vivo. Employing lymphocytic choriomeningitis virus (LCMV), we demonstrate that the cross-presentation and cross-priming of LCMV antigens were dominated by NP396, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…In another study, cross-presentation was observed only for immunodominant epitopes (22). Moreover, using the lymphocytic choriomeningitis virus (LCMV) infection model, we observed better cross-presentation for LCMV-nucleoprotein 396 (NP396) than for LCMV-glycoprotein 33 (GP33); both epitopes are immunodominant after virus infection (2). However, the cross-priming of both epitopes was comparable in vivo due to the high GP33 T cell precursor frequency (2).…”
Section: Cd8mentioning
confidence: 80%
See 4 more Smart Citations
“…In another study, cross-presentation was observed only for immunodominant epitopes (22). Moreover, using the lymphocytic choriomeningitis virus (LCMV) infection model, we observed better cross-presentation for LCMV-nucleoprotein 396 (NP396) than for LCMV-glycoprotein 33 (GP33); both epitopes are immunodominant after virus infection (2). However, the cross-priming of both epitopes was comparable in vivo due to the high GP33 T cell precursor frequency (2).…”
Section: Cd8mentioning
confidence: 80%
“…BMDC preparations were described previously, and cells were used 7 days after culturing. HEK293 or HEK-NP was used as antigen donor cells as previously described (2,5). All media were purchased from Invitrogen (Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations